Pengembangan Destinasi Pariwisata Kreatif Melalui Pasar Lumpur - Selfi Budi Helpiastuti (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract The development of creative tourism destinations has become a